2010
DOI: 10.7183/1045-6635.21.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Formative Adaptations, Diet, and Oral Health in the Azapa Valley of Northwest Chile

Abstract: Indicators of oral health were recorded in a sample of 200 Formative period (1500 B.C.–A.D. 500) skeletons from archaeological sites located in the Lower Azapa Valley of northwest Chile. This period represents a major shift in subsistence strategies in the Atacama Desert, as coastal groups adopted agriculture and moved deeper into the valley. Frequencies of caries and antemortem tooth loss were compared between site locations (coast vs. valley) and by archaeological phase (early vs. late) to interpret the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…The results obtained here appear to fit a model that involves decreased physiological stress for groups subsisting on marine resources. This result is not a novel one, as several studies have demonstrated low frequencies of skeletal stress markers with coastal habitation and subsistence in prehistory worldwide (Benfer 1990 for Peru;Tayles et al 2000 for Southeast Asia;Alfonso et al 2007and Watson et al 2010 for northern Chile; Gómez and Novellino 2011 for Argentina; and Temple 2010 for Japan).…”
Section: Coastal Habitation and Stressmentioning
confidence: 72%
See 3 more Smart Citations
“…The results obtained here appear to fit a model that involves decreased physiological stress for groups subsisting on marine resources. This result is not a novel one, as several studies have demonstrated low frequencies of skeletal stress markers with coastal habitation and subsistence in prehistory worldwide (Benfer 1990 for Peru;Tayles et al 2000 for Southeast Asia;Alfonso et al 2007and Watson et al 2010 for northern Chile; Gómez and Novellino 2011 for Argentina; and Temple 2010 for Japan).…”
Section: Coastal Habitation and Stressmentioning
confidence: 72%
“…Factors such as water contamination and overreliance on one specific food are important to understand but have yet to be fully teased out. However, the current picture suggests that when coastal populations are compared en masse to terrestrial ones, coastal populations seem to fare better in a variety of different measurements, e.g., caries rates, stature, cribra orbitalia, and linear enamel hypoplasia (Alfonso et al 2007;Benfer 1990;DiGangi 2008;Watson et al 2010). This emphasizes the role that coastal environments, in concert with cultural adaptations, play in buffering physiological stress.…”
Section: Coastal Living Advantages and Exceptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Por su parte los estudios de almidones en sarro dental de varios grupos tardíos de Arica y Camarones (PLM-4, Az-8 y Cam-9) reflejan un consumo de diversas especies vegetales (maíz y poroto, entre otros) en concordancia con las plantas ofrendadas en las tumbas (Arriaza et al 2017). Las patologías bucales (caries y pérdida de piezas dentales) también se incrementan con el desarrollo e intensificación de la agricultura, producto del consumo de maíz y otros vegetales (Alfonso et al 2007;Watson et al 2010Watson et al , 2013. Entonces también cabe preguntarse ¿cómo se comparan estos datos cualitativos con los análisis químicos que permiten una cuantificación más directa de los vegetales consumidos?…”
unclassified